2015
DOI: 10.1212/wnl.0000000000001421
|View full text |Cite
|
Sign up to set email alerts
|

Glycated albumin predicts the effect of dual and single antiplatelet therapy on recurrent stroke

Abstract: GA could be a potential biomarker to predict the effects of dual and single antiplatelet therapy in patients with minor stroke or TIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The meta‐analysis combining the CHANCE study with 13 previous studies of other populations in the world showed consistent conclusions . Later, glycated albumin level below the cut point of 15.5% implied an additional benefit of DAPT versus monotherapy, with a significant reduction in risks of stroke recurrence (adjusted HR 0.40, 95% CI 0.26–0.61, P < 0.001) and combined vascular events (adjusted HR 0.39, 95% CI 0.26–0.60, P < 0.001) and a nonelevated risk of bleeding (adjusted HR 1.87, 95% CI 0.71–4.92, P = 0.204) in a subgroup analysis of the CHANCE study with total 3044 patients . This study showed that the level of glycated albumin could be a new biomarker in antiplatelet decision‐making.…”
Section: Patients With Noncardioembolic Ischemic Strokementioning
confidence: 51%
“…The meta‐analysis combining the CHANCE study with 13 previous studies of other populations in the world showed consistent conclusions . Later, glycated albumin level below the cut point of 15.5% implied an additional benefit of DAPT versus monotherapy, with a significant reduction in risks of stroke recurrence (adjusted HR 0.40, 95% CI 0.26–0.61, P < 0.001) and combined vascular events (adjusted HR 0.39, 95% CI 0.26–0.60, P < 0.001) and a nonelevated risk of bleeding (adjusted HR 1.87, 95% CI 0.71–4.92, P = 0.204) in a subgroup analysis of the CHANCE study with total 3044 patients . This study showed that the level of glycated albumin could be a new biomarker in antiplatelet decision‐making.…”
Section: Patients With Noncardioembolic Ischemic Strokementioning
confidence: 51%
“…Blood pressure was measured in the left arm of supine patients using a mercury or electronic sphygmomanometer. Venous blood was drawn from fasting patients 24±12 hours after randomization in 3044 patients of these 73 centers 21. Plasma glucose after overnight fasting was then analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Venous blood was drawn from fasting patients 24AE12 hours after randomization in 3044 patients of these 73 centers. 21 Plasma glucose after overnight fasting was then analyzed. The serum specimens were collected and shipped on ice by overnight courier from each participating hospital to Beijing Tiantan Hospital (China), where all data analyses were performed.…”
Section: Measurementsmentioning
confidence: 99%
“…The result suggests that TIA patients with low glycated albumin level could benefit from dual antiplatelet therapy. Future studies can explore possible mechanisms of the influence of glycated albumin on the response to antiplatelet agents [41]. Another serum marker is sCD40L.…”
Section: Individualized Drug Therapy and Further Studymentioning
confidence: 99%